Associated Factors Of Metabolic Syndrome And The Role Of Oral Health Among 50 And Older Adults: from the 6th KNHANES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study on relationship between metabolic syndrome and oral health, is rare. We investigated to find out the correlation of metabolic syndrome and oral health. We investigated to find out the correlation of metabolic- syndrome and oral health with the data from the 6th Korea- National- Health and Nutrition- Examination- Survey. This is the cross-sectional designed study. 2433 subjects (aged 50 ≤) were included. Metabolic- syndrome was defined as NCEP-ATP (National- Cholesterol- Education- Program-Adult- Treatment- Panel Ⅲ). To analyze influencing factors of metabolic syndrome, multi-variable- logistic- regression was used. Our results showed that gender(male) (OR 1.86; 95%CI: 1.27-2.72; p